Combined oral contraceptives and liver cancer - Ramiro Molina (2018)
A multi‐national, hospital‐based, case‐control study was conducted to evaluate the possible relationships of steroid contraceptives to 6 neoplasms. Based on data from 122 newly diagnosed cases of primary liver cancer and 802 matched controls, the relative risk of liver cancer in women who had ever used combined oral contraceptives was estimated to be 0.71 (95% Cl 0.4–1.2). No consistent trend in risk with months of use or time since first or last use was observed. Separate analyses also revealed no association between use of combined oral contraceptives and hepatocellular carcinoma (RR = 0.60) or cholangiocarcinoma (RR = 1.22). Most women in this study came from areas in which hepatitis B is endemic and rates of liver cancer are relatively high, and in most cases use of oral contraceptives was of short duration. These results provide no evidence that short‐term use of oral contraceptives enhances risk of liver cancer in countries where the determinants of this disease are similar to those observed in the countries where this study was conducted. Copyright © 1989 Wiley‐Liss, Inc., A Wiley Company